Assessing the impact of public accounting reforms in Algeria: An analytical study of the government accounting system under the organic finance law (LOLF) - Nabila, Haillami (International journal of economic perspectives, 2024)
This study examines the impact of public accounting reforms in Algeria, particularly the transition from a cash-based accounting system to an accrual-based framework under the Organic Finance Law (LOLF) of 2018. The research assesses the limitations of the previous accounting system, which was inadequate in providing a comprehensive financial overview of public entities. The LOLF introduces significant changes in budgeting, financial accounting, and management accounting, aiming to enhance transparency, efficiency, and performance in public finance management. By aligning Algeria’s accounting practices with International Public Sector Accounting Standards (IPSAS), the LOLF seeks to improve the accuracy and reliability of financial information, thereby supporting better fiscal policy decisions and more effective resource allocation. The study also explores the challenges faced during the implementation of these reforms, including the cultural shift within public administration towards performance-based management and the complexity of developing and applying Key Performance Indicators (KPIs). The findings indicate that while the reforms have led to significant improvements in financial reporting and accountability, there are ongoing challenges that need to be addressed to fully realize the benefits of the LOLF. Recommendations include enhancing budget sincerity, refining performance measurement frameworks, and strengthening internal controls to ensure the long-term effectiveness of public financial management in Algeria.